2018
DOI: 10.1200/jgo.17.00243
|View full text |Cite
|
Sign up to set email alerts
|

Evidence From Ghana Indicates That Childhood Cancer Treatment in Sub-Saharan Africa Is Very Cost Effective: A Report From the Childhood Cancer 2030 Network

Abstract: PurposeNo published study to date has examined total cost and cost-effectiveness of maintaining a pediatric oncology treatment center in an African setting, thus limiting childhood cancer advocacy and policy efforts.MethodsWithin the Korle Bu Teaching Hospital in Accra, Ghana, costing data were gathered for all inputs related to operating a pediatric cancer unit. Cost and volume data for relevant clinical services (eg, laboratory, pathology, medications) were obtained retrospectively or prospectively. Salaries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 23 publications
4
66
1
Order By: Relevance
“…Taken together, these cost differences likely account for the significantly lower cost of treating a disease like BL in this low‐income country setting, as compared with diseases with longer or more intensive treatment regimens. Notably, a major cost category in some other economic studies of LMIC childhood cancer programs is surgical personnel and costs, which are most relevant in the treatment of pediatric solid tumors . Aside from the minimal procedural costs associated with pathologic diagnosis, such costs do not accrue in the context of BL management.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these cost differences likely account for the significantly lower cost of treating a disease like BL in this low‐income country setting, as compared with diseases with longer or more intensive treatment regimens. Notably, a major cost category in some other economic studies of LMIC childhood cancer programs is surgical personnel and costs, which are most relevant in the treatment of pediatric solid tumors . Aside from the minimal procedural costs associated with pathologic diagnosis, such costs do not accrue in the context of BL management.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have suggested that treating childhood cancer in LMICs via organized pediatric oncology units is cost‐effective . However, critically ill patients represent a significant increase in costs for inpatient care due to the need for intensive interventions, medications, and more frequent monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of health care insurance and/or a social support network, the catastrophic costs associated with a childhood cancer may lead to the abandonment of treatment in low and middle‐income countries . These lives lost, within a global society that has the knowledge, expertise, and resources to cost‐effectively treat childhood cancer represent a gross health inequality and a violation of children's human rights . Therefore, there is an urgent need to redress the existing inequities to relieve the distress imposed on families of children with cancer and to reduce their social and economic costs.…”
Section: Discussionmentioning
confidence: 99%